Agile practices and performance: Examining the role of psychological empowerment. Issue 1 (January 2021) - Malik, Mohsin; Sarwar, Shagufta; Orr, Stuart
Highlights: This study introduced and empirically tested psychological empowerment as the explanatory mechanism for the relationship between agile practices and performance. Empirical support was found for the psychological empowerment mediated relationships between team autonomy and innovative behaviour and agile communication and innovative behaviour. Innovative behaviour also affected project performance. Agile practices of team diversity and incremental and iterative development were not found to have a valid relationship with psychological empowerment. The empirical validation of agile practices as a source of empowerment and motivation for agile teams is a new finding in the literature which has strong implications for both the theory and practice. This research has also established that the difference between motivated and amotivated project teams lies in the communication and team autonomy constructs. Abstract: This study draws on the literature on psychological empowerment to conceptualize agile practices as a source of intrinsic motivation that enables the agile teams to deliver innovative outcomes. Then, drawing on the resource based view of innovative projects, the innovative behaviour of agile teams is cast as a project capability that affects project performance. To test this original conceptualization, data was collected to find support for the hypothesized relationships between agile practices, psychological empowerment, innovative behaviour and project performance. The statistical results showed that the agile practices of team autonomy and agile communication contributed to psychological empowerment that led to the innovative behaviour of agile teams. The innovative behaviour also affected project performance. The empirical validation of agile practices as a source of empowerment and motivation for agile teams is a new finding in the literature which has strong implications for both the theory and practice.